CD147-expressed small extracellular vesicles enhance the detection of colorectal neoplasia with fecal immunochemical test - L.-C. Chang; B.-R. Lin; H.-M. Chiu; M.-S. Wu; T. Ochiya; T.-L. Shen (ESMO Gastrointestinal Oncology)
Background: Blood testing increases adherence to colorectal cancer (CRC) screening. The suboptimal detection of advanced adenoma (AA) and early-stage CRC by blood tests limits their application. The current study aims to investigate the diagnostic performance of CD147-expressed small extracellular vesicles (CD147) in the serum in combination with the fecal immunochemical test (FIT) for detecting AA and CRC. Patients and methods: The case-control study enrolled 15 healthy controls and 50 CRC patients in the training cohort and 120 healthy controls, 50 non-AA patients, 50 AA patients, and 60 CRC patients in the validation cohort. CD147 was detected using the ExoScreen assay. The sensitivity and specificity of CD147 alone and combined with the FIT for detecting colorectal neoplasia were compared. Results: CD147 could detect AA and CRC with a sensitivity of 58.0% and 71.7%, respectively. Combined with a 1-day FIT, the sensitivity for detecting AA and CRC would increase to 78.0% and 93.3%, respectively. Moreover, CD147 with 1-day FIT had a higher sensitivity than 1-day FIT alone for detecting proximal CRC (100% versus 89.5%). Besides, CD147 may detect 57.7% and 50.0% of the AA and CRC that FIT failed to detect, respectively. However, the specificity and false-positive rate of CD147 were inferior to those of FIT for detecting AA and CRC. Conclusions: CD147 is superior to FIT for detecting AA and proximal neoplasia. Moreover, CD147 can increase the sensitivity of FIT for detecting either AA or CRC by combinatory use. However, false positivity is the concern of CD147, which should be further resolved in the future.